Synthesis of schiff base hydrazone from palmitic hydrazide and corrosion inhibitory properties via electrochemical methods - Mohd, Noor Khairin (2017)
In view of the emerging importance of non-toxic and green corrosion inhibitors to replace chromate (CrO42-), molybdenate (MoO3-), nitrate (NO2-) and silicate (SiO44-)in protecting metallic surfaces in acid pickling for metal processing industry, acidified oil wells and boiler cleaning process; researchers have recently focused on organic corrosion inhibitors. Schiff bases are amongst the molecules of choice that are able to exhibit corrosion inhibitory activities and have been predominantly investigated as corrosion inhibitors for numerous metals in various acidic media. The lone pair electrons and π-electrons at imine bond may interact with d-orbital of metal through electron donation and forms a layer. This layer protects the metal surface from being attacked by corrosive species. The objectives of this study are firstly to synthesize Schiff base hydrazones (SBHs) from palmitichydrazide and various aldehydes; and secondly to investigate inhibitive activities of those SBHs on mild steel in acid solution via electrochemical method. Eight SBHs were successfully synthesized from PH and various aldehydes containing linear alkyls, branched alkyl and aryls through one-pot synthesis. Commonly, acid catalyst is required in the synthesis of Schiff base as to increase electrophilicity of carbonyl for aldehyde and to allow dehydration to form Schiff base; and an efficient water removal system is applied to improve conversion. In this study, SBHs were prepared by heating the reactants in dimethyl form amide at 90oC for 2 hours without using any acid catalyst. Opportunely, SBHs with high yields (92-100%) and high purity (92-99%) were successfully obtained. The effect of solvent used, reactant mol ratio and reaction time on synthesis of SBHs were also investigated. Chemical characterization was conducted using gas chromatography, Fourier trans formed-infrared (FT-IR), CHN elemental analysis, 1H and 13C nuclear magnetic resonance and gas chromatography-mass spectroscopy. . The inhibitory properties were examined on mild steel (MS) coupons in 1 M HCl solution with concentration varied from 25, 50, 75, 100 and 200 mg/L at temperature ranged from 25 to 55oC using electrochemical techniques: linear polarization and electrochemical impedance spectroscopy as well as surface analysis using scanning electron microscopy-energy dispersive x-ray (SEM-EDX). The presence of studied inhibitors had shown appreciable inhibition efficiency (IE%) in which the increment of IE% values exceed 50% when the concentration of inhibitor and temperature were increased from 25 to 200 mg/L and 25 to 55oC, respectively. The adsorption of SBHs onto the MS surface obeyed the Langmuir adsorption isotherm with the standard free energy of adsorption (ΔGads) of between -31 and -43 kJ/mol. According to these values, these SBHs adsorbed spontaneously onto MS surface through both physisorption and chemisorption processes. Other thermodynamic parameters such as activation energy (Ea), entropy of adsorption (ΔSads),enthalpy of adsorption (ΔHads),enthalpy of activation (ΔHo) and entropy of activation (ΔSo) were also determined. SEM-EDX analysis was conducted on MS coupons after immersing in 1 M HCl solution and inhibited 1 M HCl solution containing 200 mg/L for 3 hours and 30 days. In general, significant changes of MS surface were clearly seen after 30 days of immersion. Smooth surfaces with invisible of scratch lines were observed for MS coupons obtained from experiments containing SBHs except for SBHs with a branched alkyl (HB1) and phenyl with methoxy group (HA2). In EDX analysis, significant differences in ferum, chlorine and oxygen contents were observed for MS coupons that were immersed in blank and inhibited solutions containing PH and HB1 that probably attributed to the formation of corrosion products like FeCl2and Fe(OH)2.All SBHs except for solutions containing HB1 and HA2 showed inhibitory properties that better than PH. This could be due to the lone pair of electrons on the nitrogen at imine and heteroatoms of SBHs structures. These electrons allow them to efficiently adsorb onto metal surface thus inhibiting the surface. Branching effect and incapability of phenyl group to lay flat orientation on the MS surface for HB1 and HA2 molecules, respectively could be the main reasons for these two inhibitors did not perform well as corrosion inhibitors.